Penerapan Arsitektur Organik pada Gorontalo Coffee Center - Ainun Fatha Musalam; Ernawati; Kalih Trumansyahjaya (Transbahasa, 2025)
Gorontalo is known as one of Indonesia’s coffee-producing regions, particularly for Pinogu coffee, which has been recognized as an origin coffee. However, the potential has not been fully utilized due to the lack of educational and tourism facilities that could introduce the culture, processes, and economic value of local coffee to the public and visitors. To address this challenge, the Gorontalo Coffee Center was designed with an organic architecture approach emphasizing harmony between the building and nature. The design concept incorporates natural materials, organic forms inspired by the site’s landscape, and eco-friendly spaces that provide comfort for visitors. The design method includes a literature review on organic architecture and coffee tourism, comparative studies of coffee centers in other Indonesian regions, and descriptive analysis of the site and spatial needs in Gorontalo. The design results indicate that the Gorontalo Coffee Center has the potential to become both an educational and recreational hub as well as a new tourism icon reflecting local identity. The implementation of organic architecture not only offers a design in harmony with nature but also strengthens the image of Pinogu coffee, supports coffee-based MSME development, creates new job opportunities, and boosts the regional economy based on local potential. Thus, the Gorontalo Coffee Center is expected to become a model of sustainable tourism infrastructure integrating education, recreation, and environmental preservation.